A review of paediatric cervical spinal trauma. Issue 5 (October 2018) - Brown, Philip; Munigangaiah, Sudarshan; Davidson, Neil; Bruce, Colin; Trivedi, Jayesh
Abstract: Significant spinal trauma in the paediatric population is uncommon. Cervical spine injuries account for approximately 1.5% of injuries. In paediatric patients a far higher proportion of injuries which affect the spinal column occur in the cervical spine in comparison with adults. The assessment of paediatric spinal injuries and radiographs can be challenging even for experts. This is due to a combination of the evolving osseous anatomy and the increase in ligamentous injury. This article looks at the initial assessment and management of injuries. It also presents some of the common radiographic measurements which can be used to assess spinal injuries, paediatric specific injuries of the spine and common variants confused with fractures.